Increased Resting-State Functional Connectivity of the Hippocampus in Rats With Sepsis-Associated Encephalopathy - Yao, Yue; Lu, Chunqiang; Chen, Jiu; Sun, Jie; Zhou, Cuihua; Tan, Cheng; Xian, Xian; Tong, Jianhua; Yao, Hao (Frontiers in Neuroscience, 2022)
Background: Sepsis-associated encephalopathy (SAE) has been identified as a frequent complication of sepsis, featured by an aberrant level of cognitive and affective functions. The present study is designed to explore the changes in functional connectivity (FC) of the hippocampus in rats with SAE utilizing resting-state functional magnetic resonance imaging (rs-fMRI). Methods: Sprague-Dawley rats were randomly assigned to the SAE and control groups. We acquired rs-fMRI data using a 7T MRI to evaluate hippocampal network functional differences between the two groups with a seed-based approach. Behavioral performance was assessed using the open field test and forced swimming test. Statistical analysis was undertaken to evaluate the correlation between the hippocampal FC and behavioral findings. Results: Compared with the control group, the SAE group showed increased FC between the bilateral hippocampus and thalamus, septum, bed nuclei stria terminalis (BNST), left primary forelimb somatosensory cortex (S1FL), primary motor cortex (M1) and inferior colliculus. Increased FC between the left hippocampus and thalamus, septum, BNST, left S1FL, and inferior colliculus was observed. While with the right hippocampus, FC in thalamus, septum, left S1FL and inferior colliculus was enhanced. Additionally, positive correlations were found between the hippocampal FC and the immobility time in the forced swimming test. Conclusions: Hippocampus-related brain networks have significant alterations in rats with SAE, and the elevated hippocampal resting‐state FC was positively related to affective deficits. Changes in FC between the hippocampus and other brain regions could be a potential neuroimaging biomarker of cognitive or mental disorders triggered by SAE.